ORGANIZATIONAL ASPECTS OF THE USE OF MEDICINAL PRODUCTS DRUGS IN COSMETOLOGY CLINICS (American Journal of Research in Humanities and Social Sciences, 2024)
Organizational aspects of the practical use of drugs in aesthetic medicine are relevant, first of all, due to the fact that, in general, most of the information about cosmetic injections is informal [1, 2]. Such information comes to cosmetologists from speakers at conferences, seminars and training centers and does not always correspond to the parameters, specified in the instructions for the drug used. Unfortunately, despite the fact that cosmetology develops in this way, knowledge is transferred from hand to hand, and the marketing work of supplier companies comes to the fore, the fact remains that cosmetologists rely more on the experience of their colleagues than on permits. This creates a serious problem for the management of the quality of medical care in beauty clinics.